2022
DOI: 10.3389/fnmol.2022.913328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes Associated With Prognosis in Glioblastoma

Abstract: BackgroundGlioblastoma (GBM) is the most common malignant primary brain tumor, which associated with extremely poor prognosis.MethodsData from datasets GSE16011, GSE7696, GSE50161, GSE90598 and The Cancer Genome Atlas (TCGA) were analyzed to identify differentially expressed genes (DEGs) between patients and controls. DEGs common to all five datasets were analyzed for functional enrichment and for association with overall survival using Cox regression. Candidate genes were further screened using least absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…More importantly, in terms of clinical value, ANXA2R was only reported to correlate with the prognosis of glioma patients. 55 In our study, ANXA2R showed excellent diagnostic ability for TCMR and AR. The aberrant upregulation of ANXA2R expression indicated the explosion of rejection and significantly worse graft survival for kidney transplant recipients.…”
Section: Discussionsupporting
confidence: 60%
“…More importantly, in terms of clinical value, ANXA2R was only reported to correlate with the prognosis of glioma patients. 55 In our study, ANXA2R showed excellent diagnostic ability for TCMR and AR. The aberrant upregulation of ANXA2R expression indicated the explosion of rejection and significantly worse graft survival for kidney transplant recipients.…”
Section: Discussionsupporting
confidence: 60%
“…For instance, our data identified RPS4X, RPL34, and VMP1 as having more inhibitory effects in ER + BC cells compared to ESR1 inhibition. The RPS4X ribosomal protein has been linked to numerous cancer types, including glioblastoma [ 28 ], lung adenocarcinoma [ 29 ], hepatocellular carcinoma [ 30 ], ovarian cancer [ 31 ], and many others. RPL34 is another ribosomal protein that has been implicated in several cancer types [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, TMEM60 was the gene with the highest risk score, which belongs to the transmembrane protein family (TMEM), and TMEMs are mostly involved in adverse events related to tumors, such as TMEM88 that leads to proliferation, migration, and invasion of gastric cancer tumors through the JAK2/STAT3 pathway ( 82 ). It has been previously reported that TMEM60 was closely associated with poor prognosis in GBM patients ( 83 ), but no correlation analysis was given, while Yang et al. ( 84 ) also found that high expression of TMEM60 would lead to poor prognosis in GBM patients and hypothesized that it might be related to immunosuppression.…”
Section: Discussionmentioning
confidence: 98%